2018
DOI: 10.1016/j.alit.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Barrier dysfunction in the nasal allergy

Abstract: Epithelial cells form the first physiological barrier against invasion by pathogens and the infiltration of allergens. Tight junctions (TJ), a cell-cell junctional complex located on the apical side of epithelial cells, have a critical role in the maintenance of epithelial barrier function. Impaired TJ structures are observed in patients with asthma, atopic dermatitis and nasal allergy; therefore, the dysfunction of epithelial barriers might be involved in the initiation or progression of allergic diseases. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 40 publications
3
35
0
Order By: Relevance
“…Endogenous HDAC activity was significantly greater in ALI cultures of patients compared with control subjects (Fig 1, A). In line with previous publications, 7,32 we observed that TER of ALI cultures of patients was significantly decreased compared with that in healthy control subjects (Fig 1, B). Individual patient data demonstrated that endogenous HDAC activity negatively correlated with TER of both patients and healthy control subjects (Fig 1, C).…”
Section: Endogenous Hdac Activity Is Increased In Patients With Arsupporting
confidence: 93%
“…Endogenous HDAC activity was significantly greater in ALI cultures of patients compared with control subjects (Fig 1, A). In line with previous publications, 7,32 we observed that TER of ALI cultures of patients was significantly decreased compared with that in healthy control subjects (Fig 1, B). Individual patient data demonstrated that endogenous HDAC activity negatively correlated with TER of both patients and healthy control subjects (Fig 1, C).…”
Section: Endogenous Hdac Activity Is Increased In Patients With Arsupporting
confidence: 93%
“…Differently from other studies, we found that very low (1st quartile) exposure to greenness measured by NDVI, an objective measure capturing even small-scale green spaces, was associated with a higher risk of self-reported nasal symptoms. We hypothesized that this finding might be ascribed to the lack of mitigation effect of greenness on pollutants from vehicular sources, such as diesel exhaust particles (DEP) recently shown to be involved in the oxidative stress-mediated pathway leading to the dysfunction of epithelial barriers of nasal mucosa [ 41 ]. However, we do underline that these results have to be considered with caution and cannot be generalized since NDVI is not able to identify which, if any, particular vegetation types, pathways of exposure or duration of exposures are present [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“… 58 Interestingly, these negative effects of DEP were suppressed by treatment with a reactive oxygen species scavenger. 58 , 59 A second possible mechanism of sinonasal inflammatory disease aggravation is through DEP-mediated induction of pro-inflammatory cytokines. Kim et al 60 stimulated nasal fibroblasts with DEP and performed a cytokine and chemokine array where they found increased levels of interleukin-6 (IL-6) and interleukin-8 (IL-8).…”
Section: Air Pollutants and Chronic Sinonasal Inflammatory Disorders mentioning
confidence: 99%